Plesionyms as a Vocabulary Teaching Tool: The Case of Estonian EFL Learners - Yevchuk Alina (Sciendo, 2021)
The present study investigated the effectiveness of using plesionyms, or near-synonyms, as a vocabulary teaching tool in the English as a foreign language classroom and attempted to determine at what level of proficiency this technique could be incorporated. 40 Estonian university students who were enrolled in three different ESP courses participated in the study. The students were divided into 4 groups according to their level of proficiency: one experimental and one control group consisted of B1 level students; and one experimental and one control group consisted of B2 level students. The experimental groups learned the vocabulary in plesionymic pairs by discussing the differences as well as the similarities between near-synonyms. Meanwhile, the control groups learned the same words non-adjacently, meaning that the words were taught independently and neither differences nor similarities between words were discussed. Based on the findings, it was concluded that teaching vocabulary through plesionymic pairs facilitates immediate recall and long term memory retention among B2 level students. This vocabulary teaching method could be considered more effective at more advanced levels of proficiency.